Company Zakat Distribution Model in Metro Lampung - Zainal Arifin; Nova Purnamasari (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
This article aims to describe the corporate zakat implementation model in Metro City, as implemented by the Grand Sekuntum Syariah Metro hotel. This research is a field research, data collection techniques using documentation and interviews. The analysis technique used is a qualitative technique. The results of this study indicate that the distribution of company zakat is carried out by taking into account two criteria, namely consumptive and productive. Consumptive zakat is given directly to mustahik without empowerment. This zakat is distributed directly to the underprivileged people who are around the hotel in the form of consumable needs, such as food, clothing, and housing needs in general. Meanwhile, for productive zakat distribution, the hotel cooperates with the Amil Zakat Institution in Metro City, the hotel gives its zakat funds to the amil zakat institution. The zakat funds are used to support productive zakat distribution programs in Metro City.